LITERARY AWARD UNDER FIRE (TO CRITICAL REFLECTIONS OF MAGNESIA LITERA 2019) - Hrtánek, Petr (Bohemica Olomucensia, 2020)
This essay deals with journalistic reflections of the Czech literary award Magnesia Litera as manifestations of discourse of Czech literary criticism. It shows how this award is referred in five articles published in 2019 (articles by Petr Štengl, Eva Klíčová, Roman Polách, Miroslav Balaštík and Ondřej Horák). The essay notes their thematic directions, analyzes and compares their main means of expression and used argumentation strategies.
Keywords: literary award; Magnesia Litera; literary criticism; expressions; argumentations